2023
DOI: 10.1088/1367-2630/acaf99
|View full text |Cite
|
Sign up to set email alerts
|

Dual stage approach to laser-driven helical coil proton acceleration

Abstract: Helical coil accelerators are a recent development in laser-driven ion production, acting on the intrinsically wide divergence and broadband energy spectrum of laser-accelerated protons to deliver ultra-low divergence and quasi-monoenergetic beams. The modularity of helical coil accelerators also provides the attractive prospective of multi-staging. Here we show, on a proof-of-principle basis, a two-stage configuration which allows optical tuning of the energy of the selected proton beamlet. Experimental data,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…During an experiment, the protons are emitted by the source, propagate a distance r s to the interaction region where they acquire small deflections due to the electromagnetic fields, and then travel ballistically a distance r d to the detector. In a number of experiments (Paudel et al, 2012;Ahmed et al, 2016;Obst-Huebl et al, 2018;Ferguson et al, 2023), self-probing arrangements have also been demonstrated, where the TNSA protons accelerated from a foil are used to probe phenomena initiated by the same laser pulse that has accelerated them, for instance, in parts of the same target from which they are emitted, or in the surrounding medium. The top image is of 13 MeV protons, and the bottom image is of 14.7 MeV protons.…”
Section: Diagnostic Geometry and Other Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…During an experiment, the protons are emitted by the source, propagate a distance r s to the interaction region where they acquire small deflections due to the electromagnetic fields, and then travel ballistically a distance r d to the detector. In a number of experiments (Paudel et al, 2012;Ahmed et al, 2016;Obst-Huebl et al, 2018;Ferguson et al, 2023), self-probing arrangements have also been demonstrated, where the TNSA protons accelerated from a foil are used to probe phenomena initiated by the same laser pulse that has accelerated them, for instance, in parts of the same target from which they are emitted, or in the surrounding medium. The top image is of 13 MeV protons, and the bottom image is of 14.7 MeV protons.…”
Section: Diagnostic Geometry and Other Considerationsmentioning
confidence: 99%
“…As an example, recent experiments by Zhang et al (2020) studied the electron-Weibel instability generated in a low-density gas-jet plasma using a circularly polarized laser via electron imaging with bunches of 45 MeV electrons from a linear accelerator. Efforts to image relativistic plasmas with wakefield-accelerated electron bunches were reported by Schumaker et al (2013), Zhang et al (2016), and Wan et al (2022, 2023. Schumaker et al (2013) were the first to demonstrate plasma probing applications employing wakefield-accelerated electrons, which enabled the detection of highly transient magnetic fields generated by an ultrashort, intense laser pulse on a solid target.…”
Section: A Advanced Sourcesmentioning
confidence: 99%
“…Kar et al [21] conceived a two-beam laser-triggered HC current, allowing protons to travel through the HC twice, and the maximum energy in the simulation exceeded 100 MeV. This scheme was experimentally implemented by Ferguson et al [29] . Two laser beams with energies of approximately 50 J and approximately 60 J, respectively, interact with two coil targets sequentially.…”
Section: Introductionmentioning
confidence: 99%